(untitled) (Islas, 2025)
Introduction: This article aims to analyze the work of Ramón Meza, with a special emphasis on three key aspects: his role as a chronicler and communicator of local events, his interaction with the scientist Carlos de la Torre, and the significance of the early scientific excursions in the municipality of Madruga, Cuba. Methods: A historical method with a historiographic approach was used to interpret Meza’s chronicles and their relation to the scientific figures and events of the time. The study situates his contributions within the social and economic context that influenced Madruga and integrates the cultural dimensions reflected in his writings. Results: Through his articles, Meza’s role as a chronicler and the scientific and cultural interactions in early 20th-century Madruga were examined. These writings highlight his contribution to an inclusive science connected to the local natural and cultural heritage. His collaboration with Carlos de la Torre places him within a network of intellectuals who promoted scientific dissemination in Cuba. Conclusions: Meza played a crucial role in the education of the local community by promoting the values of Madruga’s natural heritage and cultural diversity. His chronicles contribute to scientific knowledge and underscore the need for an inclusive science that considers not only technical aspects but also dialogue with local traditions and culture. His collaboration with Carlos de la Torre forms part of a broader network of Cuban intellectuals striving to make science accessible to non-specialized audiences.